The implementation of the UN Convention on the Rights of Persons with Disabilities in Austria and Germany - Ganner, Michael; rieder, elizabeth; Voithofer, Caroline; Welti, Felix (Innsbrucker Beiträge zur Rechtstatsachenforschung, 2021)
The series "Innsbrucker Beiträge zur Rechtstatsachenforschung" ("Innsbruck' contributions to empirical legal studies") aims at analysing the interconnections of law in the books and law in action with a special focus on the functioning of law. Volume 12 includes the collection of articles presented at the conference on "The implementation of the UN Convention on the Rights of Persons with Disabilities in Austria and Germany", which took place on 13th February 2020 in Innsbruck. The reasons for the conference were the almost simultaneous second state reviews of Austria and Germany on the UN CRPD. Michael Ganner (Innsbruck) and Felix Welti (Kassel) examine the state of implementation in Austria and Germany. Max Rubisch (Vienna), Valentin Aichele (Berlin) and Petra Flieger/Volker Schönwiese (Absam/Innsbruck) dedicate their contributions on the state examinations. The papers by Flieger/Schönwiese and Verena Bentele (Berlin) show the importance of self-advocacy and NGOs. Michael Ganner (Innsbruck) and Volker Lipp/Lena Baltzer/Maximilian Bresch/Pablo Hesse/René Schröder (Göttingen) shed light on the state of implementation with regard to legal subjectivity and access to justice (Arts 12, 13 UN CRPD). The right to education (Art 24 UN CRPD) is addressed by Caroline Voithofer (Innsbruck), Arne Frankenstein (Bremen), Elisabeth Rieder (Innsbruck) and Lilit Grigoryan (Kassel/Cologne). The right to work (Art 27 UN CRPD) is discussed by Hansjörg Hofer (Vienna) for Austria and Yi-Chun Chou (Taipei/Taiwan) for Japan, South Korea and Taiwan. Delia Ferri (Maynooth/Ireland) shows the influences of the UN CRPD in the European Union.